Morphology engineering of Streptomyces coelicolor M145 by sub-inhibitory concentrations of antibiotics. Issue 1 (December 2017) - Wang, Hu; Zhao, Guoping; Ding, Xiaoming
Abstract Growth ofStreptomyces in submerged culture is characterized by the formation of complex mycelial particles, known as pellets or clumps, which strongly influence antibiotic production. Also, many bioactive molecules produced byStreptomyces have great potential to modulate soil bacteria morphological development. However, there has been no effort directed at engineering mycelial morphology using these small molecules. Here, thiostrepton was identified, using a combination of qRT-PCR, semi-preparative HPLC, and MALDI-TOF MS, as a pellet-inducing compound produced byS. laurentii ATCC31255. At sub-inhibitory concentration, thiostrepton stimulatedStreptomyces coelicolor M145 pellet formation and antibiotics production were altered, with 3-fold and 2-fold decreases in actinorhodin and undecylprodigiosin yields, respectively. It was also shown that mycelial morphology can be influenced by other antibiotic class at sub-inhibitory concentrations. For instance, in the presence of spectinomycin, S. coelicolor M145, which under typical growth conditions forms large diameter pellets with many protruding hyphae, instead formed small diameter pellets with barely visible hyphae at the edge. Importantly, this morphology produced a 4-fold increase in undecylprodigiosin production and 3-fold decrease in actinorhodin production. These results indicated that these small molecules, previously identified as antimicrobials, also have great potential for influencing mycelial morphology.